Challenges of cathodic protection in high-performance concrete: The impact of electrical resistivity - Bhuiyan Shamir; Law David (MATEC Web of Conferences)
Utilization of high-performance concrete (HPC) incorporating supplementary cementitious materials (SCMs), such as fly ash and slag, is becoming increasingly popular in modern construction. While such concrete can have desirable properties such as high strengths and enhanced durability, their inherently high electrical resistivities can pose a challenge should future electrochemical treatments like cathodic protection (CP) be required. To investigate the effects of high resistivities, an experiment was undertaken where steel reinforced concrete prisms were prepared using 65% cement-replacement using ground granulated blast furnace slag (GGBS) and 30% Class F Fly Ash and were periodically subject to short term CP as the concrete dried. The test involved periodic resistivity measurements and short-term CP application while monitoring polarization of the steel bar with respect to embedded reference electrodes. The output voltage required to operate the CP in galvanostatic mode was also monitored. The results demonstrated that the resistivity of the slag specimen reached a point beyond which the power supply’s output capacity was reached. Moreover, the current distribution was observed to become less uniform as resistivity increased. This paper highlights an often-overlooked aspect of high-performance concrete incorporating SCMs, emphasizing the hypothetical yet important limitations that may arise for future electrochemical treatments if required.